Factors related to the practice of breast self examination (BSE) and Pap smear screening among Malaysian women workers in selected electronics factories - Chee, HL; Shamsuddin, K; S, Rashidah; O, Intan (BioMed Central, 2003)
Background: The Malaysian Ministry of Health promotes breast self-examination (BSE) for all women, and Pap smear screening every three years for all sexually active women ages 20 years and above. The objectives of this paper were to examine the practice of these two screening tests among women production workers in electronics factories, and to identify factors related to practice. Methods: This was a cross-sectional survey of women production workers from ten electronics factories. Data was collected by a self-administered questionnaire from a total of 1,720 women. The chi-square test, odds ratio and binomial logistic regression were used in bivariate and multivariate analysis. Results: Prevalence rates were 24.4% for BSE once a month, and 18.4% for Pap smear examination within the last three years. Women who were significantly more likely to perform BSE every month were 30 years and older, Malays, with upper secondary education and above, answered the BSE question correctly, and had a Pap smear within the last three years. The proportion of women who had a Pap smear within the last three years were significantly higher among those who were older, married, with young children, on the contraceptive pill or intra-uterine device, had a medical examination within the last five years, answered the Pap smear question correctly, and performed BSE monthly. Conclusion: Screening practice rates in this study were low when compared to national rates. Socio-demographic and health care factors significantly associated with screening practice are indicative of barriers which should be further understood so that more effective educational and promotional strategies could be developed.